PENGARUH PENERAPAN E-BILLING SYSTEM, E-FILING SYSTEM, DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DENGAN SANKSI PAJAK SEBAGAI VARIABEL MODERASI - Abi Ardiwijaya, (2022)
In achieving tax success, it takes an active role of taxpayers to comply with their tax obligations. This study aims to determine whether there is an influence from the application of the e-billing system, e-filing system, and knowledge of taxation on MSME taxpayer compliance with tax sanctions as a moderating variable. This study uses a quantitative method with the sample being individual taxpayers who are registered in the PPKUMKM Sub-department in the West Jakarta area. The sampling technique used is simple random sampling with a total sample of 100 respondents. The data was processed and tested using the Partial Least Square method with the SmartPLS 3.0 application. The results of this study indicate that the application of the e-billing system and tax knowledge has a positive and significant effect on MSME taxpayer compliance. Meanwhile, the implementation of the e-filing system has a positive but not significant effect on MSME taxpayer compliance. Tax sanctions also cannot strengthen the relationship between the e-billing system, e-filing system, and tax knowledge on MSME taxpayer compliance.